ENERAPAN SISTEM INFORMASI SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KEPUASAN KARYAWAN - TRISILO, RISMANTO GATOT (KIAT BISNIS, 2017)
This study is aimed to assess the influence of applying HRIS toward time management, cost management, quality of information effect and managerial satisfaction. Non probability sampling technique is used in taking the sample. The participants in this study are 80 HR officers from 8 companies in central Java and around. The data collection technique which is used to help this study is online questionnaire. The approach of this study is by using quantitative method, analyzing technique by using SPSS V.16. The result of this study shows that HRIS application influences time management, however applying HRIS does not influence cost management, quality of information effect and managerial satisfaction. Keyword : HRIS implementation, cost management, managerial satisfaction.